Stem cell regenerative technologies In multiple sclerosis - Faatima Jeylani (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Multiple sclerosis (MS) is an unpredictable immune system attack on the central nervous system, leaving some with the inability to see, speak, or even walk. This condition affects approximately 1.8 million people worldwide and is particularly common among females, who are often diagnosed in early adulthood. Between 2013 and 2020, the number of people diagnosed with multiple sclerosis increased by 30%. With this rapid increase in disease prevalence and detection, the need for effective treatments or a way of slowing down disease progression has become crucial. Thus far, clinical studies for neuroprotective therapies in other central nervous system diseases have had limited success. However, for multiple sclerosis, the use of stem cells provides great promise in decreasing disease progression. A stem cell transplant involves multiple sclerosis patients receiving a healthy stem cell donation. Some of the stem cell treatments include autologous haematopoietic stem cell transplantation (aHSCT) and mesenchymal cell therapy. There is evidence that haematopoietic stem cell transplantation is effective for those who have relapsing multiple sclerosis. Due to this, only those meeting specific medical criteria are offered treatment.